THE EFFECT OF SERVICE QUALITY, PRICE AND DESIGN ON CUSTOMER SATISFACTION AT PETRO DOLLAR CAFE IN LHOKSEUMAWE CITY - Cut Evi Oktaviani; T. Edyansyah; Adnan; Chalirafi (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The aim of this research is to determine and analyze jointly the influence of service quality, price and design on customer satisfaction at Cafe Petro Dollar in Lhokseumawe City. The research method is a quantitative research method. This research was conducted at the Petro Dollar Cafe in Lhokseuamwe City. The population in this research is Cafe Petro Dollar consumers, the sample used in this research was 100 respondents. The research results show that service quality (X1), price (X2), and design (X3) partially influence customer satisfaction (Y) at Cafe Petro Dollar in Lhokseumawe City. Furthermore, service quality (X1), price (X2), and design (X3) have a simultaneous and significant effect on customer satisfaction (Y) at Cafe Petro Dollar in Lhokseumawe City, because based on the F test the significance value was found to be 0.004, where the value 0.004 > 0.05, then the Fcount value is 3.552 > Ftable 2.700.